Iklan Animasi “Sebuah Kenangan Manis” Dalam Perspektif Kritik - Nawawel Sakti Aroisi, Nawawel (CITRAWIRA : Journal of Advertising and Visual Communication, 2022)
“Sebuah Kenangan Manis” comercial ads by Khong Huan company received a lot of attention and appreciation from many internet users when it was released. By using 2D animation media created using the frame by frame technique, it requires animators to draw images one by one to animate the drawings. The animation of “A Sweet Memories” interesting because it is quite rare for advertisements made by local studios to use 2D animation media with quality that can be said to compete with foreign animation. In addition, in the advertisement, Khong Huan also claims to use a Japanese animation style called anime, which in Indonesia has quite a lot of fans. In response to the many appreciations for this advertisement, this study will try to directly analyze the animation visuals of “Sebuah Kenangan Manis” advertisement by frame by frame.